1996
DOI: 10.1051/rnd:19960503
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid ducks overfed with boiled corn develop an acute hepatic steatosis with decreased choline and polyunsaturated fatty acid level in phospholipids

Abstract: Summary ― Hepatic and plasma lipid changes were investigated in hybrid ducks after steatosis was induced by overfeeding. Fourteen hybrid ducks were force-fed (11 kg corn in 13 days). The liver of the overfed ducks weighed ten times more than that of controls (695 vs 69 g). The phospholipid, ash, water and protein content of the liver were only slightly higher (2.6-, 3.6-, 4.4-and 3.2-fold, respectively) but the liver lipid concentration was 16.5 times higher after than before overfeeding (56.1 vs 3.4 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
6
14
1
Order By: Relevance
“…Indeed, translation factors (eukaryotic initiation factor 4A-II and eukaryotic translation initiation factor 2 subunit 1) were over expressed during overfeeding of ducks [35]. This is consistent with the increase in the protein quantity during the beginning of the period of fat accumulation in livers [36]. These results were also in agreement with those of Zhu et al [32] at the level of gene expression in geese.…”
Section: Liver Proteome Of Waterfowlsupporting
confidence: 89%
“…Indeed, translation factors (eukaryotic initiation factor 4A-II and eukaryotic translation initiation factor 2 subunit 1) were over expressed during overfeeding of ducks [35]. This is consistent with the increase in the protein quantity during the beginning of the period of fat accumulation in livers [36]. These results were also in agreement with those of Zhu et al [32] at the level of gene expression in geese.…”
Section: Liver Proteome Of Waterfowlsupporting
confidence: 89%
“…These authors concluded that de novo hepatic lipogenesis prevails over dietary lipid intake in overfed waterfowl, affecting lipid composition of tissues. Gabarrou et al [10] also suggested lower ∆5 and ∆6 desaturase activity. Finally, we confirmed the negative correlation between proportions of PUFA and total lipid levels in muscles previously reported by Rabot [23] in the chicken.…”
Section: Discussionmentioning
confidence: 93%
“…Gabarrou et al [32] reported that the concentration of stearic acid decreased, whereas oleic acid increased noticeably from 10 to 26.3%. The concentrations of (n-6) polyunsaturated fatty acid concentration decreased from 5 to 3.7% for linoleic acid and, more sensationally, from 18.1 to 7.1% for arachidonic acid.…”
Section: -7)mentioning
confidence: 98%